The wind in the willows - Grahame, Kenneth, 1859-1932 (Penguin Books, 2012)
"Meek little Mole, willful Ratty, Badger the perennial bachelor, and petulant Toad. Since their first appearance over a hundred years ago in 1908, they've become emblematic archetypes of eccentricity, folly, and friendship. And their misadventures--in gypsy caravans, stolen sports cars, and their beloved Wild Wood--continue to capture readers' imaginations and warm their hearts long after they grow up. Begun as a series of letters from Kenneth Grahame to his son, THE WIND IN THE WILLOWS is a timeless tale of animal cunning and human camaraderie"--